Measurement of polystyrene photodegradation rate using a quartz crystal microbalance - Abdullah N. Alodhayb (IET Nanobiotechnology)
Abstract Polystyrene is a very popular polymer utilised in the manufacture of various consumer products. This polymer is very cheap; however, after its usage, the slowness of its photodegradation leads to environmental pollution. In this report, the author presents a technique to systematically measure the rate of photodegradation of a thin polystyrene film. The said film was made to coat a quartz crystal microbalance (QCM) sensor. In order to detect polymer degradation and the reduction in the molecular weight, the resonance frequency of the sensor was monitored for 24 h. Results revealed that QCM sensor irradiation with ultraviolet light with a wavelength of 365 nm and optical power of 1.5 mW caused a quite significant change in the polymer structure.